2010
DOI: 10.1016/s0140-6736(10)60705-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual HIV-1 transmission after initiation of antiretroviral therapy: a prospective cohort analysis

Abstract: Background-High plasma HIV-1 RNA concentrations are associated with increased risk of HIV-1 transmission. Initiation of antiretroviral therapy (ART) reduces plasma HIV-1 concentrations, but little empiric data are available on the rate of sexual HIV-1 transmission from persons receiving ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
670
2
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(691 citation statements)
references
References 24 publications
11
670
2
5
Order By: Relevance
“…19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM. 25 Finally, it is possible that STD/HIV prevalence within the partner pool are related to the increases in P&S syphilis and HIV as young and minority MSM have higher rates of HIV and STD.…”
Section: Resultsmentioning
confidence: 99%
“…19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM. 25 Finally, it is possible that STD/HIV prevalence within the partner pool are related to the increases in P&S syphilis and HIV as young and minority MSM have higher rates of HIV and STD.…”
Section: Resultsmentioning
confidence: 99%
“…This finding highlights the need to identify and target HIV prevention services to discordant couples. Since treatment with ARVs has been shown to reduce the risk of HIV transmission within discordant relationships by approximately 96%, [31][32][33] programs should consider prioritizing PLHIV in sero-discordant relationships for lifelong ART initiation at CD4 counts £ 350 cells/mm 3 . In addition, where resources allow, programs should consider expanding ART initiation to HIV-positive partners with CD4 counts > 350/mm 3 as outlined in recent WHO guidelines.…”
Section: Bachanas Et Almentioning
confidence: 99%
“…30 PLHIV who inconsistently use condoms and who simultaneously have higher viral loads due to non-adherence to antiretroviral treatment (ART) or because they are not yet eligible for ART are at high risk for transmitting HIV to negative sex partners. [31][32][33] These individuals are also at higher risk for acquiring other sexually transmitted infections which could compromise their own health. 34,35 Rates of consistent condom use also vary by gender, with men reporting higher rates than women.…”
Section: Introductionmentioning
confidence: 99%
“…Les études observationnelles Sept études observationnelles ont comparé le risque de transmission du VIH au sein de couples sérodifférents (un partenaire VIH + , l'autre VIH -) en fonction du statut ARV du partenaire VIH + [10][11][12][13][14][15][16]. Six études ont montré un impact positif des ARV sur le risque de transmission du VIH, et une étude a conclu négativement (Tableau I).…”
Section: Impact Du Tasp Au Niveau Des Couples Sérodifférentsunclassified